2008
DOI: 10.1152/ajpheart.00662.2008
|View full text |Cite
|
Sign up to set email alerts
|

PER3 polymorphism and cardiac autonomic control: effects of sleep debt and circadian phase

Abstract: Viola AU, James LM, Archer SN, Dijk DJ. PER3 polymorphism and cardiac autonomic control: effects of sleep debt and circadian phase. Am J Physiol Heart Circ Physiol 295: H2156 -H2163, 2008; doi:10.1152/ajpheart.00662.2008.-A variable number tandem repeat polymorphism in the coding region of the circadian clock PERIOD3 (PER3) gene has been shown to affect sleep. Because circadian rhythms and sleep are known to modulate sympathovagal balance, we investigated whether homozygosity for this PER3 polymorphism is ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 56 publications
(63 reference statements)
4
42
0
Order By: Relevance
“…Accompanying increased slow-wave sleep in subjects homozygous for the long allele is an elevated sympathetic predominance and a reduction of parasympathetic predominance in the autonomic nervous system. 97 Both homozygosity for the long allele and a SNP in exon 18, 1148 Arg, are associated with reduced daytime sleepiness, and also sleepiness in nurses working during shifts. 61,98 On the other hand, homozygosity of the 4-repeat allele correlates with insomnia in alcohol-dependent patients.…”
Section: Per3mentioning
confidence: 99%
“…Accompanying increased slow-wave sleep in subjects homozygous for the long allele is an elevated sympathetic predominance and a reduction of parasympathetic predominance in the autonomic nervous system. 97 Both homozygosity for the long allele and a SNP in exon 18, 1148 Arg, are associated with reduced daytime sleepiness, and also sleepiness in nurses working during shifts. 61,98 On the other hand, homozygosity of the 4-repeat allele correlates with insomnia in alcohol-dependent patients.…”
Section: Per3mentioning
confidence: 99%
“…The connection between both could be viewed from the perspective of the possible effect of sleep deprivation on cardiac autonomic control, associating homozygozity in Per3 VNTR with heart rate (HR) and heart rate variability (HRV) (ref. 20 ). Although no interaction of HR and HRV with VNTR Per3 genotype was found, this polymorphism has been considered a potential marker for individual differences in the autonomic nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most surveyed Per3 polymorphisms in the last five years is the biallelic length change near the putative phosphorylation site of exon 18, composed of 4 or 5 indirect repeats. Numerous studies have linked this VNTR polymorphism to overall control of autonomic balance during sleep and wake cycles and indirectly to cardiac autonomic control [18][19][20] . However, little is known about the exact clock mechanism in cardiovascular biology, and circadian rhythms in the heart have not yet been characterized at the transcriptional level, although several studies have shown that clock genes have an important function in myocardial contractile function and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Period genes such as PER3 polymorphism have also been associated with chronodisruption. It has been demonstrated that PER3 affects the sympathovagal balance of cardiac control in sleep similar to the effect of sleep deprivation [40].…”
Section: Genetics Of Chronobiologymentioning
confidence: 96%